Permanent education for the integrality of care in the mental health network (Research, Society and Development, 2021)
Aim: To identify the difficulties faced by workers in the mental health network and to carry out permanent education activities, encouraging discussion on the movement of the Psychosocial Attention Network. Method: Action research with questionnaire application and realization of permanent education workshops with 22 workers of the mental health of Japeri, RJ, whose given were treated by analysis of thematic content. Results: were analyzed four categories: Defying giants: structure of work in mental health; Professional "unprepared" and the construction in the reflection of the practice: the large turn; Articulation: integrality and intersectoriality, a way to break inequalities; Unfolding of the research and the health permanent education workshops: reflection in action generated construction. Conclusions and implications for practice: from reflection-in-action process, barriers that fragments mental health services were analyzed, allowing the elaboration of collective proposals for intervention that promote the integral care to users.